Wilde’s French Salomé - Emily Eells (Cahiers Victoriens et Edouardiens)
This paper focuses on Wilde’s use of French in his dramatization of the Biblical story, Salomé. It argues that Wilde adopted the foreign language as a strategy for representing the taboo of incestuous and homoerotic desire, murder and necrophilia. His aesthetic objective was to produce a work belonging to the school of French decadentism and adhering to its principles of symbolism. He uses the French language as if it were a system of signs divorced from their semantic meaning, creating as pure a musical notation as verbal language can allow. A study of the manuscript versions of his play reveals his limited knowledge of French, though this paper interprets the mistakes as key to his poetic achievement. Wilde’s play is untranslatable: both the illustrator Aubrey Beardsley and the composer Richard Strauss recognized the quintessential French quality of the script, and respected it in their creative translations into another artistic genre.